Desafios para a elaboração e implementação de planos sustentáveis de mobilidade : o caso dos municípios periféricos da região metropolitana do Rio de Janeiro - Maranhão, Ígor Godeiro de Oliveira (2017)
This dissertation is an initial effort to study the main challenges of the elaboration and implementation of sustainable urban mobility plans after the law 12,587 in 2012, called the National Urban Mobility Policy (PNMU, in Portuguese). With the new law, only 171 of almost 3,400 municipalities required to prepare the plans were ready by 2015, the first deadline, later extended to 2018. Furthermore, this paper focuses on the differences between Europe and Brazil in relation to the understanding of what is a sustainable urban mobility plan, how local entities are guided to elaborate them and what are the challenges for their design, from the government’s perspective. For this, reviews of the literature, especially of official documents, are carried out and a questionnaire is applied to a set of municipalities of the Metropolitan Region of Rio de Janeiro. Among the factors that notably stand out in the Brazilian case are the lack of resources to elaborate the plan, lack of integration between levels of government and problems with lack of personnel and training of the responsible agencies, while in Europe, the fare subsidy and problems related to the data analyzed are the most serious.